The anaerobic biodegradation of emerging organic contaminants by horizontal subsurface flow constructed wetlands - H. Ilyas (IWA Publishing, 2021)
The horizontal subsurface flow constructed wetland (HFCW) is widely studied for the treatment of wastewater containing emerging organic contaminants (EOCs): pharmaceuticals, personal care products, and steroidal hormones. This study evaluates the performance of HFCW for the removal of these types of EOCs based on the data collected from peer-reviewed journal publications. In HFCW, anaerobic biodegradation is an important removal mechanism of EOCs besides their removal by the filter media (through sedimentation, adsorption, and precipitation) and plant uptake. The average removal efficiency of 18 selected EOCs ranged from 39% to 98%. The moderate to higher removal efficiency of 12 out of 18 selected EOCs in HFCW indicates the suitability of this type of constructed wetland (CW) for the treatment of wastewater containing these EOCs. The reasonably good removal (>50% in most of the cases) of these EOCs in HFCW might be due to the occurrence of anaerobic biodegradation as one of their major removal mechanisms in CWs. Although the effluent concentration of EOCs was substantially decreased after the treatment, the environmental risk posed by them was not fully reduced in most of the cases. For instance, estimated risk quotient of 11 out of 18 examined EOCs was extremely high for the effluent of HFCW. HIGHLIGHTS HFCW is widely studied for the treatment of wastewater containing EOCs.; In HFCW, anaerobic biodegradation is an important removal mechanism of EOCs.; The average removal efficiency of 18 selected EOCs was in the range of 39% to 98%.; HFCWs play a considerable role in reducing the ecological risk posed by EOCs.;